Implications of Ar-Radha'ah in Determining the Mahram of Adopted Children: A Case Study in the Syariah Court of Brunei Darussalam - Binti Mohd. Shahrenidzam, Rabiahtul Shahnazirah; Kurniawan, Cecep Soleh (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
The adoption model in society in Brunei Darussalam is adoption that follows legal procedures and adoption based on mutual agreement or without going through legal procedures. This study discusses the implications of providing breast milk to adopted children and the importance of testimony (syahadat) in proving the implementation of ar-radha'ah in the Sharia Court of Brunei Darussalam. The research approach uses qualitative. The primary data source is the officers at the Sharia Court. Data collection techniques use document studies and interviews. The results indicate that Islamic law regulates adopted children who do not have a mahram relationship with their adoptive parents, even though they have been raised since childhood. So, when the child is older, they must maintain boundaries such as aurat with their adoptive family. However, if the child is breastfed by their adoptive mother through Breast Milk can change the status of an adopted child who is not a mahram to a mahram. When a woman breastfeeds her adopted child and fulfills the ar-radha'ah requirements stipulated in Islamic law, the child will become a mahram child for her and her family. Testimony to prove the existence of ar-radha'ah between the adoptive mother and the adopted child is important because it will prove that the adoptive mother can be declared fit by the judge as an adoptive parent. The Syariah Court in Brunei Darussalam refers to the Syafi'i school of thought as the main reference based on the 1959 Constitution of Brunei Darussalam.